2011
DOI: 10.4028/www.scientific.net/amr.418-420.26
|View full text |Cite
|
Sign up to set email alerts
|

Technology Study of Polypropylene Hollow Fiber Membranes-Like Artificial Lung Made by the Melt-Spinning and Cold-Stretching Method

Abstract: Artificial lung also called as oxygenator which performs a function of exchanging O2 and removing CO2 from blood. Due to its good performance at the exchange area, oxygenation, etc, hollow fiber membranes have become the main research direction of artificial lung. Polypropylene (pp) hollow fiber membranes made by the melt-spinning and cold-stretching methods (MSCS) in this study. Through the research on the membrane manufacture process and technology optimization to prepare suitable membrane for artificially l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Traditionally, the method of melt-spinning and cold-stretching (MSCS) consists of multiple steps to produce hollow porous fibers as reported in [76]. Three typical steps were used to prepare polyethylene (PE) [77][78][79], polypropylene (PP) [80][81][82], and polyvinylidene fluoride (PVDF) [83] porous hollow fiber membranes. In the first step, melt-spinning was conducted.…”
Section: Melt Spinningmentioning
confidence: 99%
“…Traditionally, the method of melt-spinning and cold-stretching (MSCS) consists of multiple steps to produce hollow porous fibers as reported in [76]. Three typical steps were used to prepare polyethylene (PE) [77][78][79], polypropylene (PP) [80][81][82], and polyvinylidene fluoride (PVDF) [83] porous hollow fiber membranes. In the first step, melt-spinning was conducted.…”
Section: Melt Spinningmentioning
confidence: 99%
“…In the MS process, researchers studied the structural evolution of hollow membranes at different annealing temperatures [ 19 ], strength fields [ 20 ], and the effect of stretching ratio on pore size distribution [ 21 ]. Liu found that the extrusion rate and stretching temperature are the main factors for the gas flux of hollow fiber membrane as an artificial lung [ 22 ]. However, the limitations of TIPS and MS include pore diameters larger than 50 nm [ 23 , 24 , 25 , 26 ], which cannot meet the requirements of ECMO [ 27 , 28 ] for leading to plasma penetration [ 27 , 29 , 30 , 31 , 32 ], and this will pose a threat of infection to surrounding medical staff and cause dangerous biological pollution to the environment [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Micropores allow a diffusion path for nutrients into the scaffold and removal of cellular waste products. Micropores can be created after the spinning process via cold stretching, thermally induced phase separation (TIPS), or by introducing a secondary sacrificial component into the base polymer . Subsequent removal of the sacrificial component leaves a microporous network throughout the fiber wall generated by the primary polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Several methodologies to form micropores are described in published literature and patents. These include the addition of soluble additives, thermally induced phase separation, and melt spinning cold stretching …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation